Performa dan Histopatologi Ayam Broiler yang Diinfeksi dengan Salmonella pullorum Setelah Pemberian Imbuhan Pakan Mengandung Tepung Cacing Tanah (Lumbricus rubellus) - A Sofyan; H Sulendra; E Damayanti; B Sutrisno; M H Wibowo (Media Peternakan, 2010)
A study was carried out to evaluate the effect of earth worm meal (Lumbricus rubellus) added into feed additive (FA) on performance and histopathology of broilers which were infected with 1 ml/bird containing 3x108 pure culture of Salmonella pullorum orally. Broilers were tested their antibody to S. pullorum by agglutination test before the chickens were infected at 22 days of age. Treatment consisted of control without FA (R0), control with antibiotic (R1), FA contain 25% earth worm meal/EWM (R2), FA contain 50% EWM (R3), FA contain 75% EWM (R4), and FA contain 100% EWM (R5) which were periodically fed to broilers every three days at seventh days before and 10 days after infection. Treatments were arranged on completely randomized design with five treatments and four replications of four broilers each. Broilers given FA had significantly (P < 0.05) increased body weight gain and improved feed conversion ratio. Broiler treated with FA containing 25% EWM (R2) improved feed utilization compared to R1, R3, and control. Histopathology analysis showed that broilers treated with FA could reduce viscera's necrosis, especially in the liver and intestine. Lesions found in broilers which were infected S. pullorum, could be reduced by FA treatment. It is concluded that EWM can be used as feed additive to improve broilers performance.   Key words: feed additive, Lumbricus rubellus, Salmonella pullorum, broilers, histopathology